Profil Kandungan Fosfat pada Air di Daerah Aliran Sungai (DAS) Tukad Ayung, Bali - Novita Wulandari; Ima Yudha Perwira; Ni Made Ernawati (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2021)
Ayung River is the longest river in the Bali Island. There are a lot of antropogenic activities around this area. However, there is lack information about the nutrient (Phosphate) level in the water of this river. This study was aimed to observe the amount of nutrient (Phosphate) in the water of Ayung River. Water sampling was carried out in the upstream, middle stream, and downstream of Ayung River from December 2019 to January 2020. The phosphate amount was measured using Hanna HI713 reagent, Dissolved Oxygen (DO) of water was measured using Winkler method, pH of water was measured using digital pH meter, and water temperature was measured using Thermometer. The result showed that phosphate of the water was ranging from 0.3 to 0.9 mg/L. The amount of phosphate tends to be higher in the evening (0.9 mg/L) compared to that in the morning time (0.4 mg/L). The phosphate increase rate of middle stream to the downstream was higher (0.011 mg/L.km) compared to that of upstream to the middle stream (0.009 mg/L.km).